Hate Speech in Maqasid Sharia Perspective - Dwi Mayasari, Luthfiana; Adi Cahya, Akmal (Institut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2021)
According to the universal declaration of human rights, freedom of speech is fundamental rights. It is needed by human to express their feeling to each other especially towards stakeholders. The article 19 of the declaration also stated it clearly that it has guarantee for human to receive information. However, it has to be admitted that several speeches are leading human into calamity. There are cases of human violence based on national, racial, or religious hatred. It has been known there are cases in south East Asia such as the attack of Ahmadiyah and Shia community, the sealing of several religious houses, and the stateless Rohingya ethnic. Those cases are usually started by the practice of hate speech. International Convention on Civil and Political Rights (ICCPR) divines hate speech as any advocacy of national, racial, or religious hatred that constitutes incitement to discrimination, hostility or violence. Hate speech is one form of restricting freedom of speech in order to maintain social order. In Islamic literature, some scholars has categorized several kinds of speech that are prohibited according to Islamic tradition. Hujjatul Islam Al-ghazali categorized twenty kinds of speech which are prohibited by Islamic tradition. However, hate speech is not specifically included within. This research found that hate speech is consisted by several kinds of those prohibited speech. It contains the act of ridicule, insult, and curse. Moreover, it calls for the audience to hate and violence the target group. To enrich the understanding of the issue, this research use the maqasid sharia as fundamental value in Islamic law that offered by Jasser Auda. Through the method of multi-dimensions and blocking the mean which are combined by maqasid, this research emphasizes that hate speech is repugnant and it is better to be prohibited. However, the prohibition of the act should be followed by good evaluation system. Therefore, it is not abused by several groups for their private gain.